If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x/3)+10=18
We move all terms to the left:
-(x/3)+10-(18)=0
We add all the numbers together, and all the variables
-(+x/3)+10-18=0
We add all the numbers together, and all the variables
-(+x/3)-8=0
We get rid of parentheses
-x/3-8=0
We multiply all the terms by the denominator
-x-8*3=0
We add all the numbers together, and all the variables
-1x-24=0
We move all terms containing x to the left, all other terms to the right
-x=24
x=24/-1
x=-24
| 5(-2x+5)+6x=2(-2x-12-)-1 | | 4x^2+89=36x | | –9+3k=9+6k | | 2-8n=2 | | 17+4x=-13+6x | | b=10/2+251 | | -12x+37=51 | | 71+x+75=180 | | 5(a+4)+4=24 | | -6p+3p=-4-20 | | 5(-2x+5)+6x=2(-2x+12-12 | | c+1/4=3/5 | | 16=−2x−4(−2x−13) | | x/7+200=235 | | x+75+71=180 | | 50+n+n=180 | | 80+10+5x+2x+6=180 | | -22+4x-7(x-7)=+6 | | 5x–2+2x+13=180 | | −18=-3y | | 55+60+y=180 | | 18-12=5r-4r | | -5-2v=-29 | | -3x+30=63 | | 5+2(3x+1)=1+4x | | -3(2y+4)=18 | | 78=-6x+20 | | 4(u-6)-6=-3(-5u+6)-u | | f4+ 9=10 | | 13-9(2x+3)=-4(2+-3)=-4(5x+4)+2x | | 2(h-2)=-10 | | 13x-12=129 |